2020
DOI: 10.3390/jcm9082545
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiologic Outcomes of Combined Use of Biocomposite and PEEK Suture Anchors during Arthroscopic Rotator Cuff Repair: A Prospective Observational Study

Abstract: The aim of the current study was to evaluate the functional and radiologic outcomes of biocompatible non-absorbable PEEK (polyetheretherketone) and biocomposite (poly-L-lactic acid/poly(lactic-co-glycolic acid) 70% + β-tricalcium phosphate) anchors, especially in terms of perianchor cyst formation during the first six months postoperatively. We prospectively analysed 29 patients who underwent arthroscopic rotator cuff repair between March and May 2019. Both PEEK and biocomposite suture anchors were used as lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Even though the perianchor cysts are noted in PEEK anchor use, the biological effect on cuff healing and subsequent clinical outcomes appears to be largely unaffected. In a study by Lee et al, the functional and radiologic outcomes of PEEK and biocomposite (PLLA/poly(lactic-co-glycolic acid) 70% + β-tricalcium phosphate) anchors were evaluated, especially in terms of perianchor cyst formation during the first three and six months postoperatively [ 14 ]. Although the PEEK anchor had a significantly lower grade of perianchor cyst formation during the third postoperative month of follow-up, the degree of cyst formation was similar in both anchors at six months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the perianchor cysts are noted in PEEK anchor use, the biological effect on cuff healing and subsequent clinical outcomes appears to be largely unaffected. In a study by Lee et al, the functional and radiologic outcomes of PEEK and biocomposite (PLLA/poly(lactic-co-glycolic acid) 70% + β-tricalcium phosphate) anchors were evaluated, especially in terms of perianchor cyst formation during the first three and six months postoperatively [ 14 ]. Although the PEEK anchor had a significantly lower grade of perianchor cyst formation during the third postoperative month of follow-up, the degree of cyst formation was similar in both anchors at six months.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the initial increase in fluid collection during the early stages of rotator cuff healing, caused by the formation of perianchor cysts around the biocomposite anchor, these cysts gradually diminished over time. Importantly, this reduction in perianchor cysts did not have any detrimental effects on the integrity of the repaired rotator cuff or the functional outcomes of patients within the first six months [ 14 ]. The authors postulate that the high prevalence of perianchor fluid collection in the early phase of repair is probably due to anchor micromotion from the tensile load of the repaired rotator cuff [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, safe, reliable and effective fixation devices for arthroscopic Bankart repair should consist of a combination of inert material with the most suitable design. Although several ex-vivo studies compared mechanical behavior of different suture anchors available on the market [ 1 , 14 , 23 ], few clinical trials compared safety and efficacy of suture anchors having different composition and design [ 4 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [ 1 ] evaluated the functional and radiologic outcomes of biocompatible non-absorbable PEEK and biocomposite anchors used during rotator cuff repair, focusing on the rate of perianchor cyst formation during the first six months postoperatively. This paper demonstrated that the biocomposite anchor has a statistically significant tendency to form higher grades of fluid collection at 3 months after surgery, though this is usually reduced by the sixth postoperative month.…”
Section: Introductionmentioning
confidence: 99%